Magnesium Isotope Fractionation During Silicate Weathering: Constrains From Riverine Mg Isotopic Composition in the Southeastern Coastal Region of China - Tong Zhao; Wenjing Liu; Zhifang Xu (Geochemistry, Geophysics, Geosystems, 2022)
Abstract Mg isotopic composition of river water is dominantly controlled by the dissolution of both silicate and carbonate sources and a series of biogeochemical processes. However, the relative importance of source and isotopic fractionation control at basin/global scale is poorly constrained. This study presents the Mg isotopic composition of river water and suspended load in river draining silicate rocks in the southeastern coastal region of China. The fractionation effect of silicate weathering on Mg isotopes is documented in both dissolved and solid phases. Mg isotopic composition of rivers draining silicate rocks exhibit ∼0.3‰ δ26Mg difference, the release of Mg from Mg‐rich minerals and formation of clays are the dominant processes controlling Mg isotopic composition of river water. The variation of Mg isotopic compositions of suspended load is closely related to the species of secondary clays (illite and chlorite); the fractionation direction during illite and chlorite formation contrasts, isotopically heavy Mg preferentially incorporates into illite while light Mg incorporates into chlorite. Furthermore, the negative correlation between 1/Mg and Mg isotopic compositions of river water indicates the Mg re‐distribution and isotope fractionation between weathering solutions and secondary clays during silicate weathering. Such isotope fractionation‐induced Mg isotope variations could be employed to estimate the contribution of Mg from silicate weathering at basin/continental scale.